IRF2BPL Is Associated with Neurological Phenotypes - Marcogliese, Paul C.; Rosenfeld, Jill A.; Koenig, Mary Kay; Chen, Agnes H.; Dickson, Patricia I.; Vera, Moin U.; Salamon, Noriko; Infante, Elena; Poppe, Bruce; Chung, Hyung-Lok; Zuo, Zhongyuan; Kanca, Oguz; et al. (American journal of human genetics, 2018)
Interferon regulatory factor 2 binding protein-like (IRF2BPL) encodes a member of the IRF2BP family of transcriptional regulators. Currently the biological function of this gene is obscure, and the gene has not been associated with a Mendelian disease. Here we describe seven individuals who carry damaging heterozygous variants in IRF2BPL and are affected with neurological symptoms. Five individuals who carry IRF2BPL nonsense variants resulting in a premature stop codon display severe neurodevelopmental regression, hypotonia, progressive ataxia, seizures, and a lack of coordination. Two additional individuals, both with missense variants, display global developmental delay and seizures and a relatively milder phenotype than those with nonsense alleles. The IRF2BPL bioinformatics signature based on population genomics is consistent with a gene that is intolerant to variation. We show that the fruit-fly IRF2BPL ortholog, called pits (protein interacting with Ttk69 and Sin3A), is broadly detected, including in the nervous system. Complete loss of pits is lethal early in development, whereas partial knockdown with RNA interference in neurons leads to neurodegeneration, revealing a requirement for this gene in proper neuronal function and maintenance. The identified IRF2BPL nonsense variants behave as severe loss-of-function alleles in this model organism, and ectopic expression of the missense variants leads to a range of phenotypes. Taken together, our results show that IRF2BPL and pits are required in the nervous system in humans and flies, and their loss leads to a range of neurological phenotypes in both species.